Multi-Omics Integration in Mice With Parkinson’s Disease and the Intervention Effect of Cyanidin-3-O-Glucoside - Wang, Wang; Zhu, Guoxue; Wang, Yuwen; Li, Wei; Yi, Shilin; Wang, Kai; Fan, Lu; Tang, Juanjuan; Chen, Ruini (Frontiers in Aging Neuroscience, 2022)
Background: The multi-factorial degenerative disease of Parkinson’s disease (PD) is the central nervous system disease, which affects mostly older adults. To date, the research was focused on the progression of Parkinson’s disease. Simultaneously, it was confirmed the imbalances of gut microbiota is associated with the occurrence and progress of Parkinson’s disease. The accurate diagnoses and precise treatment of PD are currently deficient as a result of the absent of effective biomarkers. Methods: In this study, the pharmacodynamic study of Cyanidin-3-O-glucoside in PD mice was applied. It intends to take the “imbalance” and “balance” of intestinal microecology as the starting point to investigate the “gut-to-brain” hypothesis using metabolomics combined 16S rRNA gene sequencing methods. Simultaneously, Metabolomics analysis was implemented to acquire differential metabolites and microbiome was performed to analyze the composition and filter the remarkable altered gut microbiota at the phylum/genera level. Afterwards, metabolic pathway and functional prediction analysis of the screened differential metabolites and gut microbiota were applied using MetaboAnalyst database. In addition, Pearson correlation analysis was applied for the differential metabolites and gut microbiota. We found that Cyanidin-3-O-glucoside could protect MPTP-induced PD mice. Results: Metabolomics analysis showing that MPTP-induced dysbiosis of gut microbiota significantly altered sixty-seven. The present studies have also shown that MPTP-induced PD are related to lipid metabolism, amino acid metabolism, et al. 16S rRNA sequencing analysis indicated that 5 phyla and 22 genera were significantly altered. Furthermore, the differential gut microbiota was interrelated with amino acid metabolism, et al. The metabolites and gut microbiota network diagram revealed significantly correlations between 11 genera and 8 differential metabolites. Conclusions: In combination, this research offers potential molecular biomarkers, that should be validated for future translation into clinical applications for more accurate diagnosing Parkinson’s disease. Simultaneously, the results in this study laid a basis for further study of the association between host metabolisms, gut microbiota, and PD.